Facile one-pot magnetic modification of Enteromorpha prolifera derived biochar: Increased pore accessibility and Fe-loading enhances the removal of butachlor. (October 2021) - Xiong, Sheng; Gong, Daoxin; Deng, Yaocheng; Tang, Rongdi; Li, Ling; Zhou, Zhanpeng; Zheng, Jiangfu; Yang, Lihua; Su, Long
Highlights: The important role of pore accessibility was studied. The bigger specific surface area does not always mean higher adsorption capacity. Simultaneous treatment of Enteromorpha prolifera and butachlor hazards. The prepared biochar can recycle utilization for butachlor removal. Abstract: In this work, Enteromorpha prolifera derived magnetic biochar (MBC) is prepared for the removal of butachlor (BTR) and characterized. The NaOH added during the magnetic loading process has an activating effect and enhancing the accessibility of the pores. Based on the BET result, the importance of pore accessibility rather than the specific surface area has been proposed. The maximum adsorption capacity of BTR for MBC is 158.5 mg/g. Then, the batch experiment shows that the adsorption of MBC to BTR fitted with the quasi-second-order kinetic model. The effect factors on the BTR removal were studied. Through the result of BET, Raman, XPS and FT-IR, the mechanism of MBC adsorption of butachlor was explored. After 3 cycles, the prepared MBC has a negligible reduction in the removal capacity of BTR, which provides a reference scheme for the large-scale application of Enteromorpha prolifera and the water treatment of BTR.